E-Module Based Guided Inquiry: Business And Energy For Senior High Schools - Hendriyani, Darwita (Schrödinger: Journal of Physics Education, 2023)
Research Objectives: This study aims to develop a Guided Inquiry-based Physics module on work and energy material for class X SMA and to find out students’ perceptions of the media being developed. Methodology: This research is research development (Research and Development) using the 4D development model (Define-Design-Development-Dissemination). However, this research was only carried out up to the Development stage. The research instrument used was a student needs questionnaire. Data were analyzed using descriptive statistical analysis techniques. The subjects of this development research were students of class X IPA 3 in 2018. The resulting media has specifications in the .exe format which can be operated on a computer/laptop without installing PageFlip Professional 3D software. Main Findings: The results of the development trial show that the Physics electronic module can increase students’ interest in the Physics learning process in the material of work and energy. Based on the results of the research, it can be concluded that the Guided Inquiry-based Physics electronic module on work and energy material for class X SMA that was developed is suitable for use as an independent or additional learning medium in the learning process of students. Novelty/Originality of Research: The importance of innovation in learning is to attract students’ interest and motivation in learning, therefore, the need for new innovations carried out by teachers in learning that they are capable of teaching.